2016
DOI: 10.1159/000450788
|View full text |Cite
|
Sign up to set email alerts
|

Secretoglobin Superfamily Protein SCGB3A2 Alleviates House Dust Mite-Induced Allergic Airway Inflammation in Mice

Abstract: Background: Secretoglobin (SCGB) 3A2, a novel, lung-enriched, cytokine-like, secreted protein of small molecular weight, was demonstrated to exhibit various biological functions including anti-inflammatory, antifibrotic and growth-factor activities. Anti-inflammatory activity was uncovered using the ovalbumin-induced allergic airway inflammation model. However, further validation of this activity using knockout mice in a different allergic inflammation model is necessary in order to establish the antiallergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…This work takes a significant step forward to elucidate and describe a new pathway impacted by SCGB3A2 functioning as a tumor suppressor protein. Previously we showed that SCGB3A2 functions as an anti-inflammatory and anti-fibrotic agent in the lung ( Cai and Kimura, 2015 ; Cai et al, 2014 ; Chiba et al, 2006 ; Kido et al, 2014 ; Kurotani et al, 2011 ; Yoneda et al, 2016 ). Because SCGB3A2 is mainly secreted by club cells in lung airways, it is reasonable to assume that a primary function of SCGB3A2 is to protect the hosts from pathogens and pathogen-associated molecular patterns such as LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work takes a significant step forward to elucidate and describe a new pathway impacted by SCGB3A2 functioning as a tumor suppressor protein. Previously we showed that SCGB3A2 functions as an anti-inflammatory and anti-fibrotic agent in the lung ( Cai and Kimura, 2015 ; Cai et al, 2014 ; Chiba et al, 2006 ; Kido et al, 2014 ; Kurotani et al, 2011 ; Yoneda et al, 2016 ). Because SCGB3A2 is mainly secreted by club cells in lung airways, it is reasonable to assume that a primary function of SCGB3A2 is to protect the hosts from pathogens and pathogen-associated molecular patterns such as LPS.…”
Section: Discussionmentioning
confidence: 99%
“…A cytokine-like small secreted protein, SCGB3A2 (secretoglobin 3A2, also known as UGRP1 and HIN-2), was previously identified that is abundantly and specifically expressed in non-ciliated airway epithelial (club) cells of the trachea, bronchus, and bronchioles ( Niimi et al, 2001 ) and revealing that SCGB3A2 functions to suppress lung inflammation and fibrosis ( Cai and Kimura, 2015 ; Cai et al, 2014 ; Chiba et al, 2006 ; Kido et al, 2014 ; Kurotani et al, 2011 ; Yoneda et al, 2016 ). Although specific expression of SCGB3A2 in lung epithelial cells and its role in inflammation may imply a possible important function for SCGB3A2 in the clearance of pathogens, its role in host defense, if any, has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is that the mRNA levels of Ccr4 and Ccl17 levels were higher in HDM-treated lungs of Scgb3a2 KD animals when compared to saline-treated KD animals. This suggests a regulatory role of SCGB 3A2 in the CCR4-CCL17 pathway and confirms its anti-inflammatory mode of action [24]. …”
Section: Asthmamentioning
confidence: 60%
“…SCGB 3A2 is a small molecular weight cytokine-like, secreted protein, which was recently shown to be enriched in the murine lung and possessing a variety of pharmacological activities [23]. Yoneda et al [24] sought to validate the previously published anti-inflammatory actions of SCGB 3A2 in an HDM-induced allergic airway inflammation model using Scgb3a2 KO mice. More severe airway inflammation was observed in Scgb3a2 KO mice sensitized/challenged with HDM allergens.…”
Section: Asthmamentioning
confidence: 99%
“…4,[7][8][9][10] SCGB3A2, also called UGRP1, 6 appears to share activities similar to those of SCGB1A1. It was demonstrated to exhibit antiinflammatory, [11][12][13][14][15] growth factor, 16,17 and antifibrotic activities. [17][18][19][20] SCGB3A2 also serves as a marker for lung adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%